ANALISA, PERANCANGAN DAN SIMULASI RANGKAIAN PEREDAM RC PASIF PADA PENYALURAN SEDERHANA SISTEM TENAGA DC DENGAN MENGGUNAKAN PSPICE - Susilawati, Cecilia (Jurnal Teknik Elektro, 2007)
The sub-system interaction and instability phenomena are a common problem in theDistributesd Power System (DPS). In order to regulate the output voltage or the speed, theinternal control function of a converter known as constant power load (CPL), results in theconverter tends to draw a constant power. This phenomena cause the input impedance ofCPL has negative incremental input impedance, which tends to create instability as it isconnected to a system. This paper concerns about the compensation method used to improvethe stability ot two or more connected subsystems, consisting of and L-C filter and a CPL. Acompensation method known as passive damping network containing only RC components isexamined purposedly to eliminate and reduce the instability of the subsystem. The passivedamping network was designed and simulated using PSpice. The results show that thedesigned passive damping network suitbale for small-scale power distribution system thatcontains constant power load with power level of 1kW.Keywords: Constant Power Load, DC â DC Converter, Passive Damping Circuit